(3eHGMK Yde GdCUhds - (3YHGS Hf MSf Hf LYaQ cGTa GdZWGA, J (B1323(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3ebOeI GdhGLH (B... (3GNdJa GdCUhdjf aj hLhH ebOeI GdhGLH Ydi CbhGd jCJj GdcdGe YdjgG hbHd GdNhV ajgG hPcQ UMjMgG ef GdSbjes
(3BNQgG (B:s
(3CNQgG(B: (3fbhd Ef aj gPg GdYHGQI ecQhI heSJMH heHGM aJcQg ajeG CQGO Gdedcda GJjGfgG Ef UM efgG Ch bUO Pdc ceG dh aQV Cfg bUO GdEaWGQ aj GdSaQ dJbhjI HOfg hQGMI faSg Ch GdGTJZGd HaYd Cge ef Pdcs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3CUhd Gdabgs